The Effect of Gamma Irradiation as A Food Preservation Technology on The Shelf Life and Quality of Fresh-cut Watermelon - Adeska, Rieka Arkaninto; Octaviany, Nur; Saragih, Renaldy Bernardo; Andrianti, Retno; Ridho, Ridho; Darojati, Harum Azizah; Ariyanti, Dhita (International Journal of Applied Sciences and Smart Technologies, 2024)
Several methods for preserving food, particularly fresh fruit, aim to extend shelf life without compromising nutritional value. Food preservation technology utilizing irradiation techniques ensures food safety and stability by eliminating microbes and microorganisms while preserving nutrients. This study investigates the food preservation process using gamma irradiation, analyzes the physical changes in irradiated food over time, and examines the effects of varying gamma irradiation doses on the weight loss and shelf life of fresh-cut watermelon. The research method involves gamma irradiation at doses of 1, 1.5, 2, 2.5, and 3 kGy. Findings indicate that gamma irradiation at these doses affects the weight loss of fresh-cut watermelon. The highest weight loss, approximately 87.36%, was observed at a dose of 3 kGy, indicating significant cellular and membrane damage. Furthermore, high-dose irradiation leads to nutrient degradation and accelerates water loss, resulting in physical changes in fresh-cut watermelon, such as increased softness, wateriness, and odor.Keywords: Food irradiation, Food preservation, Watermelon.